Effect of Temperature on the Plasticity of Peripheral Hearing Sensitivity to Airborne Sound in the Male Red-Eared Slider Trachemys scripta elegans - Wang, Tongliang; Li, Handong; Chen, Bo; Cui, Jianguo; Shi, Haitao; Wang, Jichao (Frontiers in Ecology and Evolution, 2022)
Chelonians are considered the least vocally active group of extant reptiles and known as “low-frequency specialists” with a hearing range of <1.0 kHz. As they are ectothermic organisms, most of their physiological and metabolic processes are affected by temperature, which may include the auditory system responses. To investigate the influence of temperature on turtle hearing, Trachemys scripta elegans was chosen to measure the peripheral hearing sensitivity at 10, 20, 30, and 40°C (close to the upper limit of heat resistance) using the auditory brainstem response (ABR) test. An increase in temperature (from 10 to 30°C) resulted in improved hearing sensitivity (a wider hearing sensitivity bandwidth, lower threshold, and shorter latency) in T. scripta elegans. At 40°C, the hearing sensitivity bandwidth continued to increase and the latency further shortened, but the threshold sensitivity reduced in the intermediate frequency range (0.5–0.8 kHz), increased in the high-frequency range (1.0–1.3 kHz), and did not significantly change in the low-frequency range (0.2–0.4 kHz) compared to that at 30°C. Our results suggest that although the hearing range of turtles is confined to lower frequencies than that in other animal groups, turtle hearing showed exceptional thermal regulation ability, especially when the temperature was close to the upper limit of heat resistance. Temperature increases that are sensitive to high frequencies imply that the males turtles’ auditory system adapts to a high-frequency sound environment in the context of global warming. Our study is expected to spur further research on the high-temperature plasticity of hearing sensitivity in diverse taxa or in the same group with different temperature ranges. Moreover, it facilitates forecasting the adaptive evolution of the auditory system to global warming.